Effect of egg hatching weight and storage duration in Age and weight of sexual maturity of Japanese Quail (coturnix japonica) chicks. (Journal of Hama University, 2022)
The research aimed to assess the weight effect and duration of storage of incubation eggs at the age and weight of birds at the sexual maturity of Japanese Quail, and the study was conducted on 360 eggs divided into two experiments: the first experiment by Gw egg weight (180 eggs) divided into 3 T1ws (small eggs less than 10g) T2wm (average eggs 10-12g), T3wb (large eggs>12g), and the second experiment by Gd egg storage period (180 eggs) also divided into 3 treatments (3-day store)Td3, (store For 7 days)Td7, (10-day store) Td10, per treatment 3 repeaters (each repeater 20 eggs). The eggs were incubated in optimal conditions for 17 days and with the hatching process completed the chicks were transferred to a farm, where they were cared for in optimal conditions for 45 days.The study showed a significant effect (P
Keywords: Japanese Quail, sexual maturity, storage duration, egg weight.